Revista organizacional de uma agroindústria sucroalcooleira: Uma análise de conteúdo da temática ambiental - Dos Santos, Fábio Freitas [UNESP]; Morales, Angélica Góis [UNESP]; Bernardo, Cristiane Hengler Correa [UNESP] (My University, 2017)
An organization newspaper is being employed by several companies, especially by sugar-alcohol agroindustry plants, to communicate its activities to the public. Owing to the relevance that a newspaper exerts within entrepreneurship, current study analyzes the environmental theme provided by an organizational newspaper distributed by A sugar-alcohol agroindustry plant in the hinterland of the state of São Paulo, Brazil. Content analysis of seven editions of the newspaper was undertaken. Results showed that the newspaper's approach on the environmental theme may provide the public with knowledge on environmental activities and their importance for agroindustry; strategic guidelines; involvement of the public as a multiplying agent of environmental practice and the spreading of a discourse on environmental responsibility of the agroindustry for the external public.
Information journal of a sugar-alcohol agroindustry plant: A content analysis of an environmental theme
Keywords: Corporative communication; Entrepreneur newspaper; Environment; Sugar-alcohol agroindustry